Tectona grandis Capped Silver-Nanoparticle Material Effects on Microbial Strains Inducing Microbiologically Influenced Corrosion - Joshua Olusegun Okeniyi; Abimbola Patricia Idowu Popoola; Modupe Elizabeth Ojewumi; Elizabeth Toyin Okeniyi; Jacob Olumuyiwa Ikotun (International Journal of Chemical Engineering)
This paper investigates Tectona grandis capped silver nanoparticle material effects on the microbial strains inducing microbiologically influenced corrosion (MIC) of metals. Leaf-extract from Tectona grandis natural plant was used as a precursor for the synthesis of silver-nanoparticle material, which was characterised by a scanning electron microscopy having Energy Dispersion Spectroscopy (SEM + EDS) facility. Sensitivity and resistance studies by the synthesized Tectona grandis capped silver nanoparticle material on three Gram-positive and three Gram-negative, thus totalling six, MIC inducing microbial strains were then studied and compared with what was obtained from a control antibiotic chemical. Results showed that all the microbial strains studied were sensitive to the Tectona grandis capped silver nanoparticle materials whereas two strains of microbes, a Gram-positive and a Gram-negative strain, were resistant to the commercial antibiotic chemical. These results suggest positive prospects on Tectona grandis capped silver nanoparticle usage in corrosion control/protection applications on metallic materials for the microbial corrosion environment.